2022
DOI: 10.3390/jcm11051348
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Presence of Culturable Microorganisms in Clinical Samples of the Genitourinary System: Systematic Review and Experience in Specialized Care of a Regional Hospital

Abstract: The detection of emerging pathogens responsible for genitourinary infections has increased with technological advances. We conducted a systematic review of publications on the involvement of these microorganisms in genitourinary samples, and we also investigated their presence and antibiotic susceptibility in samples from patients at our regional hospital (Granada, Spain). The MEDLINE database was searched up to 31 December 2020, and a cross-sectional descriptive study was performed of results obtained in urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…There is a scarcity of research on the pathogenic potential of Alloscardovia omnicolens in the current scientific literature. Some reasons for this include the recent description of the bacterium, misdiagnosis of the actual infecting agent due to phenotypic similarity to other bacteria or inaccuracies in biochemical methods [15], the low incidence of the bacterium both as a microbiota component and as an opportunistic infectious agent [4,6,7,9,14,15,16,17,29], and the difficulty of diagnosis through traditional laboratory routines [4,[29][30][31][32]. Klein et al [31] highlight that the laboratory automation process in bacterial culture has demonstrated a significant increase in the detection rate of Alloscardovia omnicolens -ten times higher than the incidence recorded before laboratory routine changes -suggesting that this species may be underestimated as a causative pathogen of urinary tract infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a scarcity of research on the pathogenic potential of Alloscardovia omnicolens in the current scientific literature. Some reasons for this include the recent description of the bacterium, misdiagnosis of the actual infecting agent due to phenotypic similarity to other bacteria or inaccuracies in biochemical methods [15], the low incidence of the bacterium both as a microbiota component and as an opportunistic infectious agent [4,6,7,9,14,15,16,17,29], and the difficulty of diagnosis through traditional laboratory routines [4,[29][30][31][32]. Klein et al [31] highlight that the laboratory automation process in bacterial culture has demonstrated a significant increase in the detection rate of Alloscardovia omnicolens -ten times higher than the incidence recorded before laboratory routine changes -suggesting that this species may be underestimated as a causative pathogen of urinary tract infections.…”
Section: Resultsmentioning
confidence: 99%
“…The colonies are small (less than 1 mm), and signs of hemolysis may sometimes be observed after 48 hours of cultivation [1,[3][4][5]. Studies indicate that although it is rarely found colonizing humans, it is part of the gastrointestinal tract microbiota [6], urinary tract [6][7][8][9], vaginal mucosa [10][11][12][13], and oral cavity [4,[14][15][16][17]. The species has been found in dental biofilms associated with dental plaques, suggesting a potential role in their formation [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, G. vaginalis was detected in three of 38 (14%) male patients with urethritis in a Japanese study using the PCR method ( 10 ). Furthermore, in a very recent systematic review, among male patients with urethritis evaluated by real-time multiplex PCR, G. vaginalis was highlighted as the most frequent emerging microorganism with a 35.6% detection rate ( 12 ). In line with these studies, G. vaginalis was detected as the most frequent microorganism (16%) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the discussion of being the causative agent of urethritis, recent studies have shown that rare microorganisms, including G. vaginalis , may be the causative agent of urinary infection. The most important reasons why these microorganisms have not been held responsible for a urinary infection until now are misclassification because of the lack of specific phenotypic criteria and the inadequacy of conventional methods in the diagnosis of these microorganisms due to slow growth ( 12 , 14 ). There are individually reported cases of genitourinary tract infections caused by G. vaginalis , such as a 43-year-old male with prostatitis and a 36-year-old male with urinary tract infection along with bacteremia ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…No exclusion criteria were applied. Sample processing always followed the standard laboratory protocol of our hospital [ 15 ]. Matrix-assisted laser desorption ionization (MALDI) Biotyper (Bruker Daltonics, Billerica, MA, USA) or MicroScan (Beckman Coulter, Barcelona, Spain) systems were employed to identify microorganisms grown in culture, and MicroScan was used to evaluate their antibiotic susceptibility.…”
Section: Methodsmentioning
confidence: 99%